Implementation of Up Grading Learning Conception Development to Improve the Teaching Quality of MTs Teachers - Pathurohman Pathurohman (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2021)
The learning process of Al Quran Hadith that is found is still conventional, such as expository, drill or lecture. This process only emphasizes achieving curriculum demands and textual delivery rather than developing learning abilities and building individuals. The purpose of this study was to overcome the problems of learning Al Quran Hadith by using the cooperative Up grading Learning model approach. This research was designed in the form of Supervision Action Research which was carried out in two cycles, where each cycle was carried out in two to three meetings. The results of this study indicate that Up Grading Learning has a positive impact on improving the performance of Al Quran Hadith teachers. This can be seen from the increasing students' understanding of the material presented by the teacher in cycles I, II, and III, namely 65.00%, 75.00% and 85.00%, respectively. In the third cycle of classical student learning completeness has been achieved.